Do children with left ventricular noncompaction and a noncompaction-to-compaction ratio < 2 have a better prognosis? - Yi Gan; Li Luo; Jie Tian; Lingjuan Liu; Tiewei Lu (BMC, 2020)
Abstract Background Ultrasonography is commonly used to diagnose left ventricular noncompaction (LVNC). A ratio of noncompacted to compacted myocardium (NC/C ratio) > >2 is often used to diagnose LVNC. However, a large proportion of patients with noncompact myocardium have NC/C < 2, and the prognosis of these patients have not been studied. Methods We included children diagnosed with LVNC between 0 and 15 years of age from January 2007 to December 2018. LVNC was diagnosed based on Stöllberger standard when over three trabeculae were found to be associated with the interventricular recesses. A maximal end systolic ratio of noncompacted to compacted layers was NC/C ratio. Outcomes for LVNC subjects with NC/C < 2 and NC/C > 2 were compared using Kaplan-Meier methods. Results There were 124 newly diagnosed LVNC cases, classified as isolated (i-LVNC, n = 47) or non-isolated (ni-LVNC, n = 77) LVNC and NC/C > 2 (n = 43) or < 2 (n = 81). The median (interquartile range) follow-up duration was 12 (3-30) months for all patients and 16 (6-36) months for survivors. Sixteen patients with i-LVNC died during follow-up. Patients with i-LVNC and NC/C > 2 had worse survival than those with NC/C < 2 (p = 0.022). Conclusions In conclusion, during a 12-month follow-up, patients with i-LVNC with NC/C < 2 had a benign prognosis and better outcomes than those with NC/C > 2, suggesting that the former could have a more active and routine lifestyle.